Association of Virus with Cases of Rubella Studied in Toronto: Propagation of the Agent and Transmission to Monkeys - Sigurdardottir, Bergthora (1963)
Using an interference test with indicator virus Echo 11, a virus has been isolated in nine of 18 specimens from cases of typical rubella. The virus will interfere with the development of cytopathology in green monkey kidney cells with viruses Echo 11, Coxsackie B1 and B4, Poliovirus I and III (Sabin strains) and simian virus SV4. In four of five paired sera this virus was neutralized by convalescent but not by the acute phase serum, tested by interference inhibition. No cytopathology was observed in unstained cultures or in sequential cultures stained with acridine orange or fluorescent antibody. The virus was destroyed by exposure to 56° C. for 30 minutes and 15% ether at 4° C. for 24 hours, but survived with some reduction in titre at 4° C. for 24 hours. Green monkeys infected by this virus developed a macular rash, lymphadenopathy and modest rise in white blood cell count.